STRATEGI KESANTUNAN BERBAHASA PEGAWAI DAN MAHASISWA UNIVERSITAS PGRI PALEMBANG DALAM PELAYANAN AKADEMIK - Nurjanah, Ismi; Wahidy, Achmad; Agustina, Juaidah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2024)
This research describes the strategy of language civility in the academic service in the Bureau of Financial ADMINISTRATION (BAK) University Pgri Palembang which includes a strategy of positive language and negative speaking. This research uses descriptive methods and qualitative approaches. Techniques and procedures for collecting data through observations, recordings, and transcripts. Data analysis is done by transcribe the recorded data into a text form and then analyzed based on the problem formulation. Based on data analysis, the civility of the staff and students in the academic services include a positive civility strategy that is dominated by Strategioffer promise (making offers and promises) and negative civility strategy in domination by the strategy minimise the imposition (reduce strength or power threats to the face of said partner). The realization of civility strategy in the event shows that speakers and partners speak in the academic service using language-based civility when communicating.